Becoming animal : an earthly cosmology - Abram, David, 1957- (Pantheon Books, 2010)
As the climate veers toward catastrophe, the innumerable losses cascading through the biosphere make evident the need for a metamorphosis in our relation to the living land. For too long we've inured ourselves to the wild intelligence of our flesh, taking our primary truths from technologies that hold the living world at a distance. This book draws readers into their animal senses in order to explore, from within, the elemental kinship between the body and the breathing Earth. Abram shows that from the awakened perspective of the human animal, awareness (or mind) is not an exclusive possession of our species but a lucid quality of the biosphere itself-- a quality in which we, along with the oaks and the spiders, steadily participate.--From publisher description.